Solar shading : how to integrate solar shading in sustainable buildings - Beck, Wouter; Dolmans, Dick (REHVA guidebook, 2010)
Solar Shading Guidebook gives a solid background on the physics of solar radiation and its behavior in window with solar shading systems. Major focus of the Guidebook is on the effect of solar shading in the use of energy for cooling, heating and lighting. The book gives also practical guidance for selection, installation and operation of solar shading as well as future trends in integration of HVAC-systems with solar control.